Solvent for electrode mixture, electrode mixture, electrode mixture layer, electrode, and battery
Patent Information
- Application Number
- JP2026035123
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-05
- Publication Date
- 2026-10-14
AI Technical Summary
【0006】 本開示によれば、金属成分の溶出量が低減された電極合剤層を形成することができる電極合剤用溶媒を提供することができる。
Smart Images

Figure 2026167498000001 
Figure 2026167498000002 
Figure 2026167498000003
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a solvent for electrode mixtures, an electrode mixture, an electrode mixture layer, an electrode, and a battery. [Background technology]
[0002] Patent Document 1 contains: - At least one solvent, the composition of which is at least one compound excluding NMP having at least one γ-butyrolactam or γ-butyrolactone ring, wherein each of these compounds is present in a mass ratio between 0.01% and 19% (including both ends), and the sum of these compounds, individually or in combination, does not exceed 19%, and the solvent is a solvent present in a mass ratio of 50% or more. - At least one electron conductor in solid form with a ratio of 50% or less (excluding 0), composition containing It is stated. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Special Publication No. 2023-505931 [Overview of the project] [Problems that the invention aims to solve]
[0004] The present disclosure aims to provide a solvent for electrode mixtures that can form an electrode mixture layer in which the amount of metal components eluted is reduced. [Means for solving the problem]
[0005] The present disclosure provides an electrode mixture solvent containing an amide compound (A), wherein the amide compound (A) is a compound other than N-methyl-2-pyrrolidone, and the content of the amide compound (A) is 0.01 ppm by mass or more and less than 100 ppm by mass relative to the mass of the solvent. [Effects of the Invention]
[0006] According to this disclosure, it is possible to provide a solvent for electrode mixtures that can form an electrode mixture layer in which the amount of metal components eluted is reduced. [Modes for carrying out the invention]
[0007] The following describes specific embodiments of this disclosure in detail, but this disclosure is not limited to the embodiments described below.
[0008] (Solvent for electrode mixtures) The electrode mixture solvent of this disclosure contains an amide compound (A) other than N-methyl-2-pyrrolidone, and the content of the amide compound (A) is 0.01 ppm by mass or more and less than 100 ppm by mass relative to the mass of the electrode mixture solvent. By preparing an electrode mixture using an electrode mixture solvent to which a very small amount of amide compound (A) has been added, and forming the electrode mixture layer of an electrode using the obtained electrode mixture, the elution of metal components from the electrode mixture layer can be reduced, and furthermore, a battery that generates less gas and has excellent cycle characteristics can be obtained.
[0009] The content of amide compound (A) in the solvent for the electrode mixture is 0.01 ppm by mass or more and less than 100 ppm by mass, more preferably 0.03 ppm by mass or more, even more preferably 0.05 ppm by mass or more, more preferably 60 ppm by mass or less, even more preferably 30 ppm by mass or less, still more preferably 15 ppm by mass or less, and particularly preferably 7.0 ppm by mass or less, based on the mass of the solvent for the electrode mixture.
[0010] Although the mechanism of action of the effects of the invention disclosed herein is not clear, it is presumed that when the content of amide compound (A) is 0.01 ppm by mass or more, the unpaired electrons of amide compound (A) coordinate to the deficiencies in the active material, thereby reducing the elution of metal components, and when the content of amide compound (A) is less than 100 ppm by mass, battery performance can be improved without excessively decomposing the amide compound (A) itself.
[0011] The content of amide compound (A) in the electrode mixture solvent can be adjusted by the amount of amide compound (A) added to the electrode mixture solvent. The content of amide compound (A) in the electrode mixture solvent can be measured by gas chromatography-mass spectrometry of the electrode mixture solvent.
[0012] The solvent for the electrode mixture of this disclosure preferably contains N-methyl-2-pyrrolidone.
[0013] The content of N-methyl-2-pyrrolidone in the electrode mixture solvent is preferably 90.0% by mass or more, more preferably 95.0% by mass or more, even more preferably 98.0% by mass or more, preferably 100% by mass or less, and more preferably 99.5% by mass or less, relative to the mass of the electrode mixture solvent. Since the content of amide compound (A) is within the above range, even when the content of N-methyl-2-pyrrolidone is 100% by mass relative to the mass of the solvent, the electrode mixture solvent may contain amide compound (A). That is, in one embodiment, the electrode mixture solvent contains amide compound (A) and N-methyl-2-pyrrolidone, with the content of N-methyl-2-pyrrolidone being substantially 100% by mass and the content of amide compound (A) being very small. In one embodiment, the electrode mixture solvent contains only amide compound (A) and N-methyl-2-pyrrolidone, with the content of amide compound (A) being very small.
[0014] The N-methyl-2-pyrrolidone content in the electrode mixture solvent can be measured by gas chromatography-mass spectrometry.
[0015] The amide compound (A) used in the solvent for the electrode mixture of the present disclosure is an amide compound other than N-methyl-2-pyrrolidone.
[0016] The boiling point of the amide compound (A) is preferably higher than 202°C, more preferably 220°C or higher, even more preferably 240°C or higher, and the upper limit is not particularly limited, but may be 500°C or lower, 400°C or lower, or 300°C or lower. The boiling point of the amide compound (A) is preferably higher than that of N-methyl-2-pyrrolidone. By adding a very small amount of the amide compound (A) having a boiling point higher than that of N-methyl-2-pyrrolidone to N-methyl-2-pyrrolidone, elution of metal components from the electrode mixture layer can be further reduced when the electrode mixture layer of an electrode is formed using the electrode mixture, and furthermore, a battery in which gas is less likely to be generated and which has further excellent cycle characteristics can be obtained.
[0017] As the amide compound (A), the compound represented by the general formula (1): is preferable, since it can further reduce elution of metal components from the electrode mixture layer, and furthermore, can provide a battery in which gas is less likely to be generated and which has further excellent cycle characteristics.
Chemical Formula
[0018] R 1 , R 2 and R 3 have a total carbon number of 4 or less. That is, R1 , R 2 and R 3 The types of groups are selected such that the total number of carbon atoms is 4 or less. 1 , R 2 and R 3 There is no lower limit to the total number of carbon atoms, but it may be 3 or more.
[0019] R 1 , R 2 and R 3 These are independently H or a monovalent substituent. Preferred monovalent substituents are alkyl groups, alkoxyalkyl groups, acylalkyl groups, alkenyl groups, amino groups, aminoalkyl groups, or cycloalkyl groups.
[0020] R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. An acyl group is preferred as the organic group having a carbonyl group. An acyl group has the general formula: -CO-R 4 (In the formula, R 4 A group represented by (where is a methyl group or an ethyl group) is preferred.
[0021] R 1 , R 2 and R 3 Any two of these atoms may bond to form a ring. The ring may also contain heteroatoms such as oxygen atoms. The ring is preferably a saturated ring. The number of members in the ring is not particularly limited, but five members is preferred. The ring is preferably a γ-lactam ring, a γ-lactone ring, a pyrrolidine ring, or an oxazoline ring.
[0022] The amide compound (A) is preferably at least one selected from the group consisting of 2-pyrrolidone (γ-butyrolactam), N-methylpropionamide, and N-ethylpyrrolidone, and more preferably at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide. The amide compound (A) may contain two or more compounds, provided that the total content is 0.01 ppm by mass or more and less than 100 ppm by mass relative to the mass of the solvent for the electrode mixture.
[0023] The electrode mixture solvent of this disclosure may be a positive electrode mixture solvent used for the production of a positive electrode, or a negative electrode mixture solvent used for the production of a negative electrode, but it is preferable to use a positive electrode mixture solvent in that it can form an electrode mixture layer in which the amount of metal components eluted is reduced.
[0024] (Electrode mixture) An electrode mixture can be prepared using the electrode mixture solvent of this disclosure. Since the electrode mixture of this disclosure contains the above-mentioned electrode mixture solvent, it is possible to form an electrode mixture layer in which metal components are less likely to leach out, and furthermore, it is possible to form an electrode mixture layer that generates less gas and provides excellent cycle characteristics. In addition, the electrode mixture of this disclosure can also suppress gelation of the electrode mixture slurry by containing the above-mentioned electrode mixture solvent.
[0025] The electrode mixture of this disclosure may be a positive electrode mixture used for the production of a positive electrode, or a negative electrode mixture used for the production of a negative electrode, but it is preferable to be a positive electrode mixture in that it can form an electrode mixture layer in which the amount of metal components leached out is reduced.
[0026] The electrode mixture of this disclosure preferably further contains a powder electrode material.
[0027] Powder electrode materials are powder electrode materials used in batteries, and preferably contain electrode active material. Electrode active material is divided into positive electrode active material and negative electrode active material.
[0028] In one embodiment, the powder electrode material is the positive electrode active material. As the positive electrode active material, one that can electrochemically intercept and release alkali metal ions such as lithium ions and sodium ions can be used.
[0029] As the positive electrode active material, for example, a material containing an alkali metal and at least one transition metal is preferred. Specific examples include alkali metal-containing transition metal composite oxides and alkali metal-containing transition metal phosphate compounds. Among these, alkali metal-containing transition metal composite oxides that produce high voltage are particularly preferred as the positive electrode active material. Examples of alkali metal ions include lithium ions, sodium ions, potassium ions, etc. In a preferred embodiment, the alkali metal ions may be lithium ions or sodium ions. That is, in this embodiment, the alkali metal ion secondary battery is a lithium-ion secondary battery or a sodium-ion secondary battery.
[0030] As a positive electrode active material capable of electrochemically intercalating and releasing lithium ions, lithium composite oxides are preferred, and lithium transition metal composite oxides are more preferred. Lithium-containing transition metal phosphate compounds are also preferred as the positive electrode active material. It is also preferable that the positive electrode active material is a substance containing lithium and at least one transition metal, such as a lithium transition metal composite oxide or a lithium-containing transition metal phosphate compound.
[0031] The transition metals used in lithium transition metal composite oxides are preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. Specific examples of lithium transition metal composite oxides include lithium-cobalt composite oxides such as LiCoO2, lithium-nickel composite oxides such as LiNiO2, lithium-manganese composite oxides such as LiMnO2, LiMn2O4, and Li2MnO3, and those in which some of the transition metal atoms that make up the main body of these lithium transition metal composite oxides are substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mg, Ga, Zr, and Si. Examples of the above-mentioned substituted materials include lithium-nickel-manganese composite oxides, lithium-nickel-cobalt-aluminum composite oxides, lithium-nickel-cobalt-manganese composite oxides, lithium-manganese-aluminum composite oxides, lithium-titanium composite oxides, and more specifically, LiNi 0.5 Mn 0.5 O2, LiLiLi 0.85 Co 0.10 Al 0.05 O2, LiLiLi 0.33 Co 0.33 Mn 0.33 O2, LiLiLi 0.5 Mn 0.3 Co 0.2 O2, LiLiLi 0.6 Mn 0.2 Co 0.2 O2, LiLiLi 0.8 Mn 0.1 Co 0.1 O2, LiMn 1.8 Al 0.2 O4, LiMn 1.5 Ni 0.5 O4, Li4Ti5O 12 Li Limited 0.82 Co 0.15 Al 0.03 Examples include O2.
[0032] Preferred transition metals for lithium-containing transition metal phosphate compounds include V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. Specific examples of lithium-containing transition metal phosphate compounds include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, and LiFeP2O7, cobalt phosphates such as LiCoPO4, and those in which some of the transition metal atoms that make up the main component of these lithium transition metal phosphate compounds are substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mg, Ga, Zr, Nb, and Si.
[0033] In particular, from the viewpoint of high voltage, high energy density, or charge / discharge cycle characteristics, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.82 Co 0.15 Al 0.03 O2, LiLiLi 0.33 Mn 0.33 Co 0.33 O2, LiLiLi 0.5 Mn 0.3 Co 0.2 O2, LiLiLi 0.6 Mn 0.2 Co 0.2 O2, LiLiLi 0.8 Mn 0.1 Co 0.1 O2 and LiFePO4 are preferred.
[0034] Furthermore, lithium-nickel composite oxides are preferred as lithium composite oxides. General formula (7): Li y Ni 1-x M x O2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) Lithium-nickel composite oxides represented by [formula] are more preferable. Lithium transition metal composite oxides with such a high nickel content are beneficial for increasing the capacity of secondary batteries.
[0035] In General Formula (7), x is a coefficient satisfying 0.01≦x≦0.7, and since a secondary battery with higher capacity can be obtained, x is preferably 0.01≦x≦0.5, more preferably 0.05≦x≦0.4, and even more preferably 0.10≦x≦0.3.
[0036] In General Formula (7), examples of the metal atom for M include V, Ti, Cr, Mn, Fe, Co, Cu, Al, Zn, Mg, Ga, Zr, Si, and the like. As the metal atom for M, a transition metal such as V, Ti, Cr, Mn, Fe, Co, Cu, or a combination of the above transition metal with another metal such as Al, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Mg, Ga, Zr, Si is preferable.
[0037] Examples of the lithium transition metal composite oxide having a high nickel content include LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.33 Mn 0.33 Co 0.33 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, and at least one selected from the group consisting of LiNi 0.90 Mn 0.05 Co 0.05 O2 is preferable, and at least one selected from the group consisting of LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, and LiNi 0.8 Mn 0.1 Co 0.1 O2 is more preferable.
[0038] As the positive electrode active material capable of electrochemically occluding and releasing sodium ions, for example, General formula (8): Na z M 0 O2 (In the formula, z is 0.01<z≦1, and M 0 represents a metal atom (excluding Na).) The sodium composite oxide represented by is preferred.
[0039] In general formula (8), z represents the composition ratio of Na and is a coefficient satisfying 0.01<z≦1. M 0 is preferably a transition metal, and examples thereof include V, Ti, Cr, Mn, Fe, Co, Ni, and Cu.
[0040] Further, as the positive electrode active material capable of electrochemically occluding and releasing sodium ions, for example, General formula (8-1): M a Mn 2-b M 1 b O4 (In the formula, M is Na; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge), a sodium-manganese spinel composite oxide represented by General formula (8-2): MNi 1-c M 2 c O2 (In the formula, M is Na; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge), a sodium-nickel composite oxide represented by, or General formula (8-3): MCo 1-d M 3 d O2 (In the formula, M is Na; 0≦d≦0.5; M 3(This refers to at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge.) Examples include sodium-cobalt composite oxides represented by [formula].
[0041] In particular, NaCoO2, NaMnO2, NaNiO2, NaMn2O4, and NaNi are chosen because they offer high energy density and can provide high-output secondary batteries. 0.8 Co 0.15 Al 0.05 O2, Na(Ni 0.33 Fe 0.33 Mn 0.33 )O2, or NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 is preferred, and it is preferable that the compound is represented by the following formula (8-4). General formula (8-4): MNi h Co i Mn j M 5 k O2 (In the formula, M is Na, M 5 (where represents at least one element selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.0, and 0≦k≦0.2.)
[0042] Examples of alkali metal-containing transition metal phosphate compounds include, General formula (8-5):M e M 4 f (PO4) g (In the formula, M is Na, M 4 (where e represents at least one element selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni, and Cu, and is represented by the formula 0.5≦e≦3, 1≦f≦2, 1≦g≦3)
[0043] Preferred transition metals for sodium-containing transition metal phosphate compounds include V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. Specific examples include NaFePO4, Na3Fe2(PO4)3, NaFeP2O7, iron phosphates such as Na3V2(PO4)3, cobalt phosphates such as NaCoPO4, and those in which some of the transition metal atoms that make up the main component of these sodium transition metal phosphate compounds are substituted with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0044] As the sodium-containing transition metal phosphate compound, one having an olivine-type structure is preferred.
[0045] Other cathode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 Examples include O4, MV3O6, M2MnO3, and Prussian blue analogs such as MFe[Fe(CN)6] (where M is Na). In particular, MNi 0.5 Mn 1.5 Positive electrode active materials such as O4 are preferable because their crystal structure does not collapse when the secondary battery is operated at a voltage exceeding 4.4V or a voltage of 4.6V or higher.
[0046] Other positive electrode active materials include M2MnO3 and MM 6 O2(wherein M is at least one metal selected from the group consisting of Li, Na, and K, M 6 Examples include solid solution materials with transition metals such as Co, Ni, Mn, and Fe.
[0047] Examples of the solid solution material include the general formula M x [Mn (1-y) M 7 y ]O z It is an alkali metal manganese oxide represented by the formula, where M is Na, and M7 is composed of at least one metal element other than M and Mn, and contains, for example, one or two or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr and Sn. Further, the values of x, y, z in the formula are in the ranges of 1<x<2, 0≦y<1, and 1.5<z<3.
[0048] Further, it is also possible to use a material in which a substance having a composition different from that of the substance constituting the main positive electrode active material is attached to the surface of these positive electrode active materials. Examples of the surface-attached substances include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.
[0049] These surface-attached substances can be attached to the surface of the positive electrode active material by, for example, a method of dissolving or suspending them in a solvent, impregnating and adding the mixture to the positive electrode active material, followed by drying; a method of dissolving or suspending a surface-attached substance precursor in a solvent, impregnating and adding the mixture to the positive electrode active material, followed by reaction by heating or the like; or a method of adding the precursor to the positive electrode active material precursor and firing them simultaneously.
[0050] The amount of the surface-attached substance used is, by mass relative to the positive electrode active material, preferably 0.1 ppm or more, more preferably 1 ppm or more, still more preferably 10 ppm or more as the lower limit, and preferably 20% or less, more preferably 10% or less, still more preferably 5% or less as the upper limit. The surface-attached substance can suppress the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material and improve the battery life. However, if the attached amount is too small, the effect cannot be sufficiently exhibited, and if the attached amount is too large, the entry and exit of alkali metal ions such as lithium ions and sodium ions may be inhibited, which may increase the resistance.
[0051] The particle shapes of the positive electrode active material can be conventionally shaped as lumps, polyhedrons, spheres, ellipsoids, plates, needles, columns, etc., but among these, it is preferable that the active material is composed of primary particles that aggregate to form secondary particles, and that these secondary particles are spherical or ellipsoidal in shape. Normally, in electrochemical elements, the active material in the electrode expands and contracts with charging and discharging, making it susceptible to deterioration such as destruction of the active material or breakage of the conductive path due to this stress. Therefore, it is preferable to have an active material in which primary particles aggregate to form secondary particles rather than a single-particle active material consisting only of primary particles, as this reduces the stress of expansion and contraction and prevents deterioration. Furthermore, spherical or ellipsoidal particles are preferable to plate-shaped equiaxially oriented particles because they require less orientation during electrode molding, resulting in less expansion and contraction of the electrode during charging and discharging, and they are also easier to mix uniformly with conductive additives when manufacturing the electrode.
[0052] The tap density of the positive electrode active material is typically 1.3 g / cm³. 3 Preferably 1.5 g / cm³ 3 More preferably 1.6 g / cm³ 3 In summary, the most preferred amount is 1.7 g / cm³. 3 The above is a summary. If the tap density of the positive electrode active material falls below the above lower limit, the amount of dispersion medium required during the formation of the positive electrode mixture layer increases, as does the amount of conductive additives and binders needed, which can restrict the packing rate of the positive electrode active material into the positive electrode mixture layer and limit the battery capacity. By using metal composite oxide powder with a high tap density, a high-density positive electrode mixture layer can be formed. Generally, a higher tap density is preferable and there is no particular upper limit, but if it is too high, the diffusion of alkali metal ions such as lithium ions and sodium ions using the non-aqueous electrolyte as a medium within the positive electrode mixture layer becomes the rate-limiting factor, which can easily degrade the load characteristics. Therefore, it is usually 2.5 g / cm³. 3 Preferably, 2.4 g / cm³ 3 The following applies:
[0053] The tap density of the positive electrode active material was determined by passing it through a sieve with a mesh size of 300 μm over 20 cm. 3After dropping the sample into the tapping cell to fill the cell volume, a powder density analyzer (for example, a Tapdenser manufactured by Seishin Corporation) is used to perform 1000 taps with a stroke length of 10 mm. The density obtained from the volume and weight of the sample at that time is defined as the tap density.
[0054] The median diameter d50 of the positive electrode active material particles (or secondary particle diameter if primary particles aggregate to form secondary particles) is typically 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, most preferably 3 μm or more, and typically 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, and most preferably 15 μm or less. If it falls below the lower limit, it may not be possible to obtain a high bulk density product, and if it exceeds the upper limit, the diffusion of alkali metals such as lithium and sodium within the particles will take time, which may lead to a decrease in battery performance or problems such as streaking when manufacturing the positive electrode of the battery, i.e., when the active material and conductive additives and binders are slurryed with a solvent and applied as a thin film. Here, the packing performance during positive electrode manufacturing can be further improved by mixing two or more positive electrode active materials with different median diameters d50.
[0055] In this disclosure, the median diameter d50 is measured using a known laser diffraction / scattering particle size distribution analyzer. When using the HORIBA LA-920 as the particle size distribution analyzer, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used as the dispersion medium during measurement, and the measurement is performed after ultrasonic dispersion for 5 minutes with a measurement refractive index of 1.24.
[0056] When primary particles aggregate to form secondary particles, the average primary particle diameter of the positive electrode active material is typically 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, most preferably 0.1 μm or more, and typically 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. Exceeding the above upper limit makes it difficult to form spherical secondary particles, which can adversely affect powder packing properties and significantly reduce the specific surface area, potentially leading to a decrease in battery performance such as output characteristics. Conversely, below the above lower limit usually results in problems such as poor reversibility of charge and discharge due to underdeveloped crystals. The primary particle diameter is measured by observation using a scanning electron microscope (SEM). Specifically, it is determined by taking a photograph at 10,000x magnification, finding the longest value of the intercept between the left and right boundaries of the primary particle with respect to a horizontal line for any 50 primary particles, and taking the average value.
[0057] The BET specific surface area of the positive electrode active material is 0.2 m². 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 For values of / g or more, 4.0m 2 Less than or equal to / g, preferably 2.5m 2 / g or less, more preferably 1.5m 2 It is less than / g. If the BET specific surface area is smaller than this range, battery performance tends to decrease, and if it is larger, it becomes difficult to increase the tap density, which can cause problems with the coating properties when forming the positive electrode mixture layer.
[0058] The BET specific surface area is defined as the value measured by the nitrogen adsorption BET single-point method using the gas flow method, after pre-drying the sample at 150°C for 30 minutes under nitrogen flow using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), and then using a nitrogen-helium mixed gas that has been precisely adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.
[0059] For the production of positive electrode active materials, general methods for producing inorganic compounds are used. In particular, various methods can be considered for producing spherical or ellipsoidal active materials. For example, a method is to dissolve or grind and disperse transition metal raw materials such as transition metal nitrates and sulfates, and raw materials of other elements as needed, in a solvent such as water, adjust the pH while stirring to produce and recover spherical precursors, dry them as needed, and then add a Li source such as LiOH, Li2CO3, or LiNO3 and calcine at a high temperature to obtain the active material. Alternatively, a method is to dissolve or grind transition metal raw materials such as transition metal nitrates, sulfates, hydroxides, and oxides, and raw materials of other elements as needed, in a solvent such as water. One method involves dispersing the material, drying and molding it with a spray dryer or the like to form a spherical or ellipsoidal precursor, adding a Li source such as LiOH, Li2CO3, or LiNO3, and firing it at a high temperature to obtain the active material. Another method involves dissolving or pulverizing and dispersing transition metal raw materials such as transition metal nitrates, sulfates, hydroxides, or oxides, a Li source such as LiOH, Li2CO3, or LiNO3, and raw materials of other elements as needed, in a solvent such as water, drying and molding the mixture with a spray dryer or the like to form a spherical or ellipsoidal precursor, and firing it at a high temperature to obtain the active material.
[0060] In this disclosure, the positive electrode active material may be used alone, or two or more materials with different compositions or different powder properties may be used in any combination and ratio.
[0061] In one embodiment, the powder electrode material is a negative electrode active material. Examples of negative electrode active materials include those that exhibit a potential of 2.5V or less relative to Li when alloyed with or bonded with Li.
[0062] As the negative electrode active material, a negative electrode active material containing a metal can be used. The metal contained in the negative electrode active material is usually a metal that can be electrochemically alloyed with alkali metals such as Li and Na.
[0063] Examples of the negative electrode active material include simple metals capable of electrochemically alloying with Li, such as Si, Zn, Sn, W, Al, Sb, Ge, Bi, and In; alloys containing Si, Zn, Sn, W, Al, Sb, Ge, Bi, In, and the like; lithium alloys such as lithium-aluminum alloys and lithium-tin alloys; metal oxides such as tin oxide and silicon oxide; and lithium titanate. As the negative electrode active material, one type or two or more types selected from these can be used.
[0064] As the negative electrode active material, a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti is preferred, and Si (simple Si), oxides of Si, alloys containing Si, Sn (Sn carrier), oxides of Sn and alloys containing Sn are more preferred, and Si and SiO x At least one selected from the group consisting of (0<x<2) is even more preferred.
[0065] Furthermore, carbonaceous materials such as graphite powder may be used as the negative electrode active material. Carbonaceous materials can be used together with negative electrode active materials containing metal. Carbonaceous materials include natural graphite, artificial carbonaceous materials, artificial graphitized materials, carbonaceous materials {for example, natural graphite, coal coke, petroleum coke, coal pitch, petroleum pitch, or these pitches that have been oxidized, needle coke, pitch coke and carbon materials that have been partially graphitized, furnace black, acetylene black, Ketjen black, pitch-based carbon fibers and other pyrolysis products of organic materials, carbonizable organic materials (for example, coal tar pitch from soft pitch to hard pitch, or coal-based heavy oils such as carbonized liquefied oil, straight-run heavy oils such as atmospheric residue and vacuum residue, crude oil, ethylene tar and other cracked petroleum heavy oils produced as by-products during the pyrolysis of naphtha, etc., as well as aromatic hydrocarbons such as acenaphthylene, decacyclene, anthracene, and phenanthrene, N-ring compounds such as phenazine and acridine, S-ring compounds such as thiophene and bithiophene, biphenyl, terpheni Examples include polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, immobilized products thereof, nitrogen-containing organic polymers such as polyacrylonitrile and polypyrrole, sulfur-containing organic polymers such as polythiophene and polystyrene, natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalacturonic acid, chitosan, and saccharose, thermoplastic resins such as polyphenylene sulfide and polyphenylene oxide, thermosetting resins such as furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin, and carbonized organic materials thereof, or solutions obtained by dissolving these in low molecular weight organic solvents such as benzene, toluene, xylene, quinoline, and n-hexane, and carbonaceous materials (e.g., hard carbon) obtained by heat-treating these carbonized organic materials once or more at a temperature range of 400 to 3200°C.
[0066] When the negative electrode mixture contains a negative electrode active material containing a metal and a carbonaceous material, the mass ratio of the negative electrode active material containing the metal to the carbonaceous material is preferably 1 / 99 to 99 / 1, more preferably 5 / 95 to 95 / 5, and even more preferably 10 / 10 to 90 / 10.
[0067] In one embodiment, the powder electrode material is a conductive additive. Preferably, the conductive additive is at least one selected from the group consisting of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphene. Examples of carbon black include acetylene black and Ketjenblack.
[0068] The electrode mixture of this disclosure preferably further contains a binder.
[0069] The binder preferably contains a fluorine-containing polymer that contains vinylidene fluoride (VdF) units.
[0070] As the fluorine-containing polymer, at least one selected from the group consisting of polyvinylidene fluoride (PVdF) and fluorine-containing copolymers containing VdF units and other monomer units other than VdF is preferred.
[0071] The fluorine-containing copolymer contains VdF units and other monomer units other than VdF. The other monomers may be fluorinated monomers or non-fluorinated monomers.
[0072] Examples of fluorinated monomers (excluding VdF) include tetrafluoroethylene (TFE), vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropene, and trans-1,3,3,3-tetrafluoropropene.
[0073] As the fluoroalkyl vinyl ether, a fluoroalkyl vinyl ether having a fluoroalkyl group with 1 to 5 carbon atoms is preferred, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether), and perfluoro(propyl vinyl ether) is more preferred.
[0074] As the fluorinated monomer, at least one selected from the group consisting of TFE, CTFE, 2,3,3,3-tetrafluoropropene, HFP, and fluoroalkyl vinyl ether is preferred, at least one selected from the group consisting of TFE and HFP is more preferred, and TFE is particularly preferred.
[0075] Fluorinated monomers (except VdF) may or may not have polar groups.
[0076] Examples of non-fluorinated monomers include non-fluorinated monomers that do not have polar groups, such as ethylene and propylene, and non-fluorinated monomers that have polar groups (hereinafter sometimes referred to as polar group-containing monomers).
[0077] When a non-fluorinated monomer having a polar group is used, the polar group is introduced into the fluorine-containing copolymer, thereby providing even better adhesion between the coated layer and the metal foil. The polar group is preferably at least one selected from the group consisting of carbonyl group-containing groups, epoxy groups, hydroxyl groups, sulfonic acid groups, sulfate groups, phosphoric acid groups, amino groups, amide groups, and alkoxy groups; more preferably at least one selected from the group consisting of carbonyl group-containing groups, epoxy groups, and hydroxyl groups; and even more preferably a carbonyl group-containing group. The above hydroxyl group does not include hydroxyl groups that constitute part of the above carbonyl group-containing group. Furthermore, the above amino group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary or secondary amine.
[0078] The carbonyl group-containing group mentioned above is a functional group having a carbonyl group (-C(=O)-). The carbonyl group-containing group is preferably a group represented by the general formula: -COOR (where R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group) or a carboxylic acid anhydride group, and more preferably a group represented by the general formula: -COOR. The number of carbon atoms in the alkyl group and hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3. Specific examples of groups represented by the general formula: -COOR include -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, -COOC2H5, etc. If the group represented by the general formula: -COOR is -COOH or contains -COOH, then -COOH may be a carboxylate salt such as a metal carboxylate salt or an ammonium carboxylate salt.
[0079] Furthermore, the carbonyl group-containing group may also be a group represented by the general formula: -X-COOR (where X is an atomic group whose main chain consists of 1 to 20 atoms and has a molecular weight of 500 or less, and R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3.
[0080] The amide group described above is preferably a group represented by the general formula: -CO-NRR' (where R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group), or a bond represented by the general formula: -CO-NR”- (where R represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted phenyl group).
[0081] The above polar group-containing monomers include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; alkylidenemalonate esters such as dimethyl methylidenemalonate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylic acid esters such as acryloyloxyethyl succinic acid, acryloyloxypropyl succinic acid, methacryloyloxyethyl succinic acid, acryloyloxyethyl phthalic acid, and methacryloyloxyethyl phthalic acid; monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; general formula (4): [ka] (In the formula, R 11 ~R 13 R independently represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. 14 Y represents a single bond or a hydrocarbon group with 1 to 8 carbon atoms. 1 represents inorganic cations and / or organic cations. Examples include monomers represented by (4); unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; etc.
[0082] As the polar group-containing monomer units that the fluorine-containing copolymer may contain, units based on monomer (4) represented by general formula (4) are preferred.
[0083] In general formula (4), Y 1 '' represents inorganic cations and / or organic cations. Examples of inorganic cations include H, Li, Na, K, Mg, Ca, Al, and Fe. Examples of organic cations include NH4 and NH3R. 15 NH2R 15 2. NHR 15 3. NR 15 4(R15 Each independently represents an alkyl group having 1 to 4 carbon atoms. Examples of cations include Y. 1 Preferred cations are H, Li, Na, K, Mg, Ca, Al, and NH4; more preferred are H, Li, Na, K, Mg, Al, and NH4; even more preferred are H, Li, Al, and NH4; and particularly preferred is H. For convenience, specific examples of inorganic and organic cations are listed without symbols or valencies.
[0084] In general formula (4), R 11 ~R 13 R independently represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. The hydrocarbon group is a monovalent hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 4 or less. Examples of the hydrocarbon group include alkyl groups, alkenyl groups, alkynyl groups, etc., with methyl or ethyl groups being preferred. 11 and R 12 R is preferably independently a hydrogen atom, a methyl group, or an ethyl group. 13 It is preferable that this is a hydrogen atom or a methyl group.
[0085] In general formula (4), R 14 The symbol represents a single bond or a hydrocarbon group having 1 to 8 carbon atoms. The hydrocarbon group is a divalent hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 4 or less. Examples of the hydrocarbon group include alkylene groups and alkenylene groups with the above number of carbon atoms, and among these, at least one selected from the group consisting of methylene, ethylene, ethylidene, propyridene, and isopropylidene groups is preferred, with methylene being more preferred.
[0086] The monomer (4) is preferably at least one selected from the group consisting of (meth)acrylic acid and its salts, vinylacetic acid (3-butenic acid) and its salts, 3-pentenoic acid and its salts, 4-pentenoic acid and its salts, 3-hexenoic acid and its salts, 4-heptenoic acid and its salts, and 5-hexenoic acid and its salts.
[0087] Other preferred monomers include at least one selected from the group consisting of TFE, CTFE, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, HFP, and fluoroalkyl vinyl ethers. (Meth)acrylic acid includes acrylic acid and methacrylic acid.
[0088] The content of other monomer units in the fluorine-containing copolymer is preferably 0.0001 to 50.0 mol%, more preferably 0.01 mol% or more, even more preferably 0.10 mol% or more, more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, and particularly preferably 35.0 mol% or less, relative to the total monomer units.
[0089] The VdF unit content of the fluorine-containing copolymer is 50.0 to 99.9999 mol%, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 99.99 mol% or less, and even more preferably 99.90 mol% or less, relative to the total monomer units.
[0090] When a fluorine-containing copolymer contains fluorinated monomer units as other monomer units, the content of fluorinated monomer units is preferably 0.0001 to 50.0 mol%, more preferably 2.0 mol% or more, even more preferably 3.0 mol% or more, particularly preferably 4.0 mol% or more, more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, particularly preferably 35.0 mol% or less, and most preferably 25.0 mol% or less, relative to the total monomer units.
[0091] When a fluorinated copolymer contains fluorinated monomer units as other monomer units, the VdF unit content of the fluorinated copolymer is 50.0 to 99.999 mol%, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, most preferably 75.0 mol% or more, more preferably 98.0 mol% or less, even more preferably 97.0 mol% or less, and particularly preferably 96.0 mol% or less, based on the total monomer units.
[0092] When a fluorine-containing copolymer contains non-fluorinated monomer units such as polar group-containing monomers as other monomer units, the content of non-fluorinated monomer units is preferably 0.0001 to 50.0 mol%, more preferably 0.01 mol% or more, even more preferably 0.10 mol% or more, more preferably 5.0 mol% or less, even more preferably 3.0 mol% or less, and particularly preferably 1.5 mol% or less, relative to the total monomer units.
[0093] When a fluorine-containing copolymer contains non-fluorinated monomer units as other monomer units, the VdF unit content of the fluorine-containing copolymer is preferably 50.0 to 99.999 mol%, more preferably 95.0 mol% or more, even more preferably 97.0 mol% or more, particularly preferably 98.5 mol% or more, more preferably 99.99 mol% or less, and even more preferably 99.90 mol% or less, relative to the total monomer units.
[0094] In this disclosure, the composition of the fluorine-containing copolymer is, for example, 19 It can be measured by 1F-NMR. Furthermore, if the fluorine-containing copolymer contains polar group-containing monomer units as other monomer units, the content of the polar group-containing monomer units can be measured, for example, by acid-base titration of the acid group if the polar group is an acidic group such as a carboxylic acid.
[0095] The weight-average molecular weight (in polystyrene equivalent) of the fluorine-containing copolymer is preferably 10,000 to 3,000,000, more preferably 30,000 or more, even more preferably 50,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less. The weight-average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as the solvent.
[0096] The number-average molecular weight (in polystyrene equivalent) of the fluorine-containing copolymer is preferably 7,000 to 1,500,000, more preferably 21,000 or more, even more preferably 35,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number-average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as the solvent.
[0097] Examples of fluorine-containing copolymers include VdF / (meth)acrylic acid copolymer, VdF / TFE copolymer, VdF / HFP copolymer, VdF / fluoroalkyl vinyl ether copolymer, VdF / TFE / HFP copolymer, VdF / 2,3,3,3-tetrafluoropropene copolymer, VdF / TFE / 2,3,3,3-tetrafluoropropene copolymer, VdF / TFE / (meth)acrylic acid copolymer, VdF / HFP / (meth)acrylic acid copolymer, VdF / CTFE copolymer, and VdF / TFE / 4-pente Examples include benzoic acid copolymers, VdF / TFE / 3-butenoic acid copolymers, VdF / TFE / HFP / (meth)acrylic acid copolymers, VdF / TFE / HFP / 4-pentenoic acid copolymers, VdF / TFE / HFP / 3-butenoic acid copolymers, VdF / TFE / 2-carboxyethyl acrylate copolymers, VdF / TFE / HFP / 2-carboxyethyl acrylate copolymers, VdF / TFE / acryloyloxyethyl succinic acid copolymers, and VdF / TFE / HFP / acryloyloxyethyl succinic acid copolymers.
[0098] As the fluorine-containing copolymer, at least one selected from the group consisting of VdF / TFE copolymer, VdF / CTFE copolymer, VdF / (meth)acrylic acid copolymer, VdF / 2,3,3,3-tetrafluoropropene copolymer, VdF / HFP copolymer, and VdF / fluoroalkyl vinyl ether copolymer is preferred.
[0099] The VdF / TFE copolymer contains VdF units and TFE units. By using the VdF / TFE copolymer as the copolymer, compositions can be formed very easily, compositions with excellent slurry stability can be obtained, and coating layers with excellent flexibility can be formed. The VdF unit content is preferably 50.0 to 95.0 mol%, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, more preferably 92.0 mol% or less, and even more preferably 89.0 mol% or less, relative to the total monomer units of the VdF / TFE copolymer. The TFE unit content is preferably 50.0 to 5.0 mol%, more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, more preferably 8.0 mol% or more, and even more preferably 11.0 mol% or more, relative to the total monomer units of the VdF / TFE copolymer.
[0100] The VdF / TFE copolymer may contain units based on monomers copolymerizable with VdF and TFE (excluding VdF and TFE) in addition to VdF and TFE units. From the viewpoint of resistance to electrolyte swelling, the content of units based on monomers copolymerizable with VdF and TFE is preferably 3.0 mol% or less relative to the total monomer units of the VdF / TFE copolymer.
[0101] Examples of monomers copolymerizable with VdF and TFE include the fluorinated monomers and the non-fluorinated monomers mentioned above. Among the monomers copolymerizable with VdF and TFE, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, and at least one selected from the group consisting of HFP, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred.
[0102] The weight-average molecular weight (polystyrene equivalent) of the VdF / TFE copolymer is preferably 50,000 to 2,000,000, more preferably 80,000 to 1,700,000, and even more preferably 100,000 to 1,500,000.
[0103] The number-average molecular weight (polystyrene equivalent) of the VdF / TFE copolymer is 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0104] The VdF / CTFE copolymer contains VdF units and CTFE units. By using the VdF / CTFE copolymer as the copolymer, compositions can be formed very easily, and a coating layer that adheres extremely firmly to the metal foil can be formed. The VdF unit content is preferably 80.0 to 98.0 mol%, more preferably 85.0 mol% or more, even more preferably 90.0 mol% or more, more preferably 97.5 mol% or less, and still more preferably 97.0 mol% or less, relative to the total monomer units of the VdF / CTFE copolymer. The CTFE unit content is preferably 20.0 to 2.0 mol%, more preferably 15.0 mol% or less, even more preferably 10.0 mol% or less, more preferably 2.5 mol% or more, and still more preferably 3.0 mol% or more, relative to the total monomer units of the VdF / CTFE copolymer.
[0105] The VdF / CTFE copolymer may contain units based on monomers copolymerizable with VdF and CTFE (excluding VdF and CTFE) in addition to VdF and CTFE units. From the viewpoint of resistance to electrolyte swelling, the content of units based on monomers copolymerizable with VdF and CTFE is preferably 3.0 mol% or less relative to the total monomer units of the VdF / CTFE copolymer.
[0106] Monomers copolymerizable with VdF and CTFE include the fluorinated monomers and non-fluorinated monomers mentioned above. Among the monomers copolymerizable with VdF and CTFE, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, at least one selected from the group consisting of TFE, HFP, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred, and TFE is even more preferred.
[0107] The weight-average molecular weight (polystyrene equivalent) of the VdF / CTFE copolymer is preferably 50,000 to 2,000,000, more preferably 80,000 to 1,700,000, and even more preferably 100,000 to 1,500,000.
[0108] The number-average molecular weight (polystyrene equivalent) of the VdF / CTFE copolymer is preferably 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0109] The VdF / (meth)acrylic acid copolymer contains VdF units and (meth)acrylic acid units. By using the VdF / (meth)acrylic acid copolymer as the copolymer, compositions can be formed very easily, and a coating layer that adheres extremely firmly to the metal foil can be formed. The content of (meth)acrylic acid units is preferably 0.0001 to 5.0 mol%, more preferably 0.01 to 3.0 mol%, and even more preferably 0.10 to 1.5 mol%, relative to the total monomer units.
[0110] The VdF unit content of the VdF / (meth)acrylic acid copolymer is preferably 95.0 to 99.9999 mol%, more preferably 97.0 to 99.99 mol%, and even more preferably 98.5 to 99.90 mol%, relative to the total monomer units.
[0111] The weight-average molecular weight (in polystyrene equivalent) of the VdF / (meth)acrylic acid copolymer is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less.
[0112] The number-average molecular weight (polystyrene equivalent) of the VdF / (meth)acrylic acid copolymer is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less.
[0113] The VdF / 2,3,3,3-tetrafluoropropene copolymer contains VdF units and 2,3,3,3-tetrafluoropropene units. By using the VdF / 2,3,3,3-tetrafluoropropene copolymer as the copolymer, compositions can be formed very easily, and coating layers with excellent flexibility and conductivity can be formed. The VdF unit content is preferably 50.0 to 98.0 mol%, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 97.0 mol% or less, and even more preferably 96.0 mol% or less, relative to the total monomer units of the VdF / 2,3,3,3-tetrafluoropropene copolymer. The content of 2,3,3,3-tetrafluoropropene units is preferably 2.0 to 50.0 mol%, more preferably 3.0 mol% or more, even more preferably 4.0 mol% or more, more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, and particularly preferably 35.0 mol% or less, relative to the total monomer units of the VdF / 2,3,3,3-tetrafluoropropene copolymer.
[0114] The VdF / 2,3,3,3-tetrafluoropropene copolymer may contain units based on monomers copolymerizable with VdF and 2,3,3,3-tetrafluoropropene (excluding VdF and 2,3,3,3-tetrafluoropropene), in addition to VdF units and 2,3,3,3-tetrafluoropropene units. From the viewpoint of resistance to electrolyte swelling, the content of units based on monomers copolymerizable with VdF and 2,3,3,3-tetrafluoropropene is preferably 3.0 mol% or less relative to the total monomer units of the VdF / 2,3,3,3-tetrafluoropropene copolymer.
[0115] Monomers that can copolymerize with VdF and 2,3,3,3-tetrafluoropropene include the fluorinated monomers and the non-fluorinated monomers mentioned above. Among the monomers copolymerizable with VdF and 2,3,3,3-tetrafluoropropene, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, and at least one selected from the group consisting of TFE, HFP and monomer (4) is more preferred.
[0116] The weight-average molecular weight (on a polystyrene basis) of the VdF / 2,3,3,3-tetrafluoropropene copolymer is preferably 10,000 to 2,000,000, more preferably 30,000 to 1,700,000, and even more preferably 50,000 to 1,500,000.
[0117] The number-average molecular weight (polystyrene equivalent) of the VdF / 2,3,3,3-tetrafluoropropene copolymer is preferably 7,000 to 1,400,000, more preferably 21,000 to 1,300,000, and even more preferably 35,000 to 1,200,000.
[0118] The VdF / HFP copolymer contains VdF units and HFP units. By using the VdF / HFP copolymer as the copolymer, compositions can be formed very easily, and a coating layer that adheres extremely firmly to the metal foil can be formed. The VdF unit content is preferably 80.0 to 98.0 mol%, more preferably 83.0 mol% or more, even more preferably 85.0 mol% or more, more preferably 97.0 mol% or less, and even more preferably 96.0 mol% or less, relative to the total monomer units of the VdF / HFP copolymer. The HFP unit content is preferably 20.0 to 2.0 mol%, more preferably 17.0 mol% or less, even more preferably 15.0 mol% or less, more preferably 3.0 mol% or more, and even more preferably 4.0 mol% or more, relative to the total monomer units of the VdF / HFP copolymer.
[0119] The VdF / HFP copolymer may contain units based on monomers copolymerizable with VdF and HFP (excluding VdF and HFP) in addition to VdF and HFP units. From the viewpoint of resistance to electrolyte swelling, the content of units based on monomers copolymerizable with VdF and HFP is preferably 3.0 mol% or less relative to the total monomer units of the VdF / HFP copolymer.
[0120] Examples of monomers copolymerizable with VdF and HFP include the fluorinated monomers and the non-fluorinated monomers mentioned above. Among the monomers copolymerizable with VdF and HFP, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, at least one selected from the group consisting of TFE, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred, and monomer (4) is even more preferred.
[0121] The weight-average molecular weight (polystyrene equivalent) of the VdF / HFP copolymer is preferably 50,000 to 2,000,000, more preferably 80,000 to 1,700,000, and even more preferably 100,000 to 1,500,000.
[0122] The number-average molecular weight (polystyrene equivalent) of the VdF / HFP copolymer is preferably 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0123] The VdF / fluoroalkyl vinyl ether copolymer contains VdF units and fluoroalkyl vinyl ether units. The VdF unit content is preferably 80.0 to 98.0 mol%, more preferably 83.0 mol% or more, even more preferably 85.0 mol% or more, more preferably 97.0 mol% or less, and even more preferably 96.0 mol% or less, relative to the total monomer units of the VdF / fluoroalkyl vinyl ether copolymer. The fluoroalkyl vinyl ether unit content is preferably 20.0 to 2.0 mol%, more preferably 17.0 mol% or less, even more preferably 15.0 mol% or less, more preferably 3.0 mol% or more, and even more preferably 4.0 mol% or more, relative to the total monomer units of the VdF / fluoroalkyl vinyl ether copolymer.
[0124] The VdF / fluoroalkyl vinyl ether copolymer may contain units based on monomers copolymerizable with VdF and fluoroalkyl vinyl ether (excluding VdF and fluoroalkyl vinyl ether), in addition to VdF units and fluoroalkyl vinyl ether units. From the viewpoint of resistance to electrolyte swelling, the content of units based on monomers copolymerizable with VdF and fluoroalkyl vinyl ether is preferably 3.0 mol% or less relative to the total monomer units of the VdF / fluoroalkyl vinyl ether copolymer.
[0125] Monomers copolymerizable with VdF and fluoroalkyl vinyl ethers include the fluorinated monomers and non-fluorinated monomers mentioned above. Among the monomers copolymerizable with VdF and fluoroalkyl vinyl ethers, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, at least one selected from the group consisting of TFE, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred, and monomer (4) is even more preferred.
[0126] The weight-average molecular weight (on a polystyrene basis) of the VdF / fluoroalkyl vinyl ether copolymer is preferably 50,000 to 2,000,000, more preferably 80,000 to 1,700,000, and even more preferably 100,000 to 1,500,000.
[0127] The number-average molecular weight (on a polystyrene basis) of the VdF / fluoroalkyl vinyl ether copolymer is preferably 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0128] The binder may also preferably contain PVdF. PVdF is a polymer containing VdF units and is a polymer different from the fluorine-containing copolymer described above. PVdF may be a VdF homopolymer consisting only of VdF units, or it may be a polymer containing VdF units and units based on monomers copolymerizable with VdF.
[0129] In the above-mentioned PVdF, the monomer copolymerizable with VdF is preferably a monomer different from tetrafluoroethylene (TFE). That is, it is preferable that PVdF does not contain TFE units.
[0130] In the above PVdF, monomers copolymerizable with VdF include fluorinated monomers and non-fluorinated monomers, with fluorinated monomers being preferred. Examples of fluorinated monomers include vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropene, and trans-1,3,3,3-tetrafluoropropene. Examples of non-fluorinated monomers include ethylene and propylene.
[0131] In the above PVdF, the monomer copolymerizable with VdF is preferably at least one fluorinated monomer selected from the group consisting of CTFE, fluoroalkyl vinyl ether, HFP, and 2,3,3,3-tetrafluoropropene, and more preferably at least one fluorinated monomer selected from the group consisting of CTFE, HFP, and fluoroalkyl vinyl ether.
[0132] In the above PVdF, the content of monomer units copolymerizable with VdF is preferably 0 to 5.0 mol%, more preferably 0 to 3.0 mol%, relative to the total monomer units. In the above PVdF, the content of fluorinated monomer units copolymerizable with VdF is preferably less than 5.0 mol%, more preferably less than 3.0 mol%, and even more preferably less than 1.0 mol%, relative to the total monomer units.
[0133] In this disclosure, the composition of PVdF is, for example, 19 It can be measured by F-NMR.
[0134] The above PVdF may have a polar group. The above polar group is not particularly limited as long as it is a polar functional group, but at least one selected from the group consisting of carbonyl group-containing groups, epoxy groups, hydroxyl groups, sulfonic acid groups, sulfate groups, phosphoric acid groups, amino groups, amide groups, and alkoxy groups is preferred, at least one selected from the group consisting of carbonyl group-containing groups, epoxy groups, and hydroxyl groups is more preferred, and a carbonyl group-containing group is even more preferred. The above hydroxyl group does not include hydroxyl groups that constitute part of the above carbonyl group-containing group. Furthermore, the above amino group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary or secondary amine.
[0135] The carbonyl group-containing group mentioned above is a functional group having a carbonyl group (-C(=O)-). The carbonyl group-containing group is preferably a group represented by the general formula: -COOR (where R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group) or a carboxylic acid anhydride group, and more preferably a group represented by the general formula: -COOR. The number of carbon atoms in the alkyl group and hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3. Specific examples of groups represented by the general formula: -COOR include -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, -COOC2H5, etc. If the group represented by the general formula: -COOR is -COOH or contains -COOH, then -COOH may be a carboxylate salt such as a metal carboxylate salt or an ammonium carboxylate salt.
[0136] Furthermore, the carbonyl group-containing group may also be a group represented by the general formula: -X-COOR (where X is composed of a main chain with 2 to 15 atoms, and the molecular weight of the atomic group represented by X is preferably 350 or less. R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3.
[0137] The amide group described above is preferably a group represented by the general formula: -CO-NRR' (where R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group), or a bond represented by the general formula: -CO-NR”- (where R represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted phenyl group).
[0138] The above polar group can be introduced into PVdF by polymerizing VdF with a monomer having the above polar group (hereinafter referred to as a polar group-containing monomer), or by reacting PVdF with a compound having the above polar group. However, from the viewpoint of productivity, polymerizing VdF with the above polar group-containing monomer is preferable.
[0139] Polymerizing VdF with the polar group-containing monomer yields PVdF containing VdF units and polar group-containing monomer units. In other words, PVdF preferably contains the polar group-containing monomer units. The content of the polar group-containing monomer units is preferably 0.001 to 5.0 mol%, more preferably 0.01 to 3.0 mol%, and even more preferably 0.10 to 1.5 mol%, relative to the total monomer units.
[0140] In this disclosure, the content of polar group-containing monomer units in PVdF can be measured, for example, by acid-base titration of the acid group when the polar group is an acid group such as a carboxylic acid.
[0141] Examples of the polar group-containing monomers include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinyl acetate (3-butenoic acid), 3-pentenoic acid, 4-pentenoic acid, 3-hexenoic acid, and 4-heptenoic acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidenemalonic acid esters such as dimethyl methylidenemalonate; and vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether. Examples include carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylic acid esters such as acryloyloxyethyl succinic acid, methacryloyloxyethyl succinic acid, acryloyloxyethyl phthalic acid, acryloyloxypropyl succinic acid, and methacryloyloxyethyl phthalic acid; monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; and the like.
[0142] When introducing the polar group into PVdF by reacting PVdF with the compound having the polar group, the compound having the polar group can be a monomer containing the polar group, or a silane-based coupling agent or titanate-based coupling agent having a group reactive with PVdF and a hydrolyzable group. The hydrolyzable group is preferably an alkoxy group. When using a coupling agent, the polar group can be added to PVdF by reacting it with PVdF that has been dissolved or swollen in a solvent.
[0143] Alternatively, PVdF can be obtained by partially defluorinating PVdF with a base, and then further reacting the partially defluorinated PVdF with an oxidizing agent. Examples of the oxidizing agents include hydrogen peroxide, hypochlorite, palladium halide, chromium halide, alkali metal permanganate, peracid compounds, alkyl peroxide, and alkyl persulfate.
[0144] The VdF unit content of PVdF is preferably more than 95.0 mol%, more preferably more than 97.0 mol%, and even more preferably more than 99.0 mol%, relative to the total monomer units. Furthermore, the VdF unit content of PVdF is preferably 95.0 to 99.999 mol%, more preferably 97.0 mol% or more, even more preferably 98.5 mol% or more, even more preferably 99.99 mol% or less, and even more preferably 99.90 mol% or less, relative to the total monomer units.
[0145] The weight-average molecular weight (polystyrene equivalent) of PVdF is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less. The weight-average molecular weight can be measured by gel permeation chromatography (GPC) using N,N-dimethylformamide as the solvent. The weight-average molecular weight of PVdF may also be 1,000,000 or more, or 1,500,000 or more.
[0146] The number-average molecular weight (polystyrene equivalent) of PVdF is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number-average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as the solvent.
[0147] The melting point of PVdF is preferably 100 to 240°C. This melting point can be determined using a differential scanning calorimetry (DSC) device as the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10°C / min.
[0148] The binder may also preferably contain a fluorine-containing copolymer as a fluorine-containing polymer, which includes PVdF and VdF units and other monomer units other than VdF.
[0149] When the binder contains PVdF and a fluorine-containing copolymer, the mass ratio of PVdF to the fluorine-containing copolymer in the binder (PVdF / fluorine-containing copolymer) is preferably 99 / 1 to 1 / 99, more preferably 97 / 3 to 3 / 97, even more preferably 95 / 5 to 5 / 95, especially preferably 90 / 10 to 10 / 90, particularly preferably 85 / 15 to 15 / 85, and most preferably 80 / 20 to 40 / 60. Alternatively, the mass ratio (PVdF / fluorine-containing copolymer) may be 90 / 10 to 60 / 40 or 85 / 15 to 65 / 35.
[0150] The binder may contain other polymers in addition to PVdF and fluorine-containing copolymers. Examples of other polymers include polymethacrylate, polymethyl methacrylate, polyacrylonitrile, polyimide, polyamide, polyamide-imide, polycarbonate, styrene rubber, and butadiene rubber.
[0151] The electrode mixture may contain dispersants such as resins with surfactant properties, cationic surfactants, or nonionic surfactants to improve slurry stability.
[0152] The total mass of the powder electrode material and binder in the electrode mixture is preferably 40% by mass or more, more preferably 55% by mass or more, even more preferably 70% by mass or more, preferably 90% by mass or less, and even more preferably 80% by mass or less, relative to the mass of the electrode mixture.
[0153] The ratio of electrode active material to conductive additive in the powder electrode material is preferably 80:20 to 99.6:0.4 by mass ratio, and more preferably 90:10 to 99.5:0.5.
[0154] The ratio of powder electrode material to binder in the electrode mixture is preferably 80:20 to 99.5:0.5 by mass ratio, more preferably 90:10 to 99.5:0.5, and even more preferably 95:5 to 99.5:0.5, and is determined considering the retention of powder components, adhesion to the current collector, and conductivity of the electrode.
[0155] The content of amide compound (A) in the electrode mixture is 0.005 to 50 ppm by mass, more preferably 0.01 ppm or more, even more preferably 0.05 ppm or more, more preferably 40 ppm or less by mass, even more preferably 10 ppm or less by mass, still more preferably 5.0 ppm or less by mass, and particularly preferably 2.0 ppm or less by mass, relative to the total mass of amide compound (A), powder electrode material, and binder.
[0156] The content of amide compound (A) in the electrode mixture can be measured by gas chromatography-mass spectrometry.
[0157] An electrode mixture can be prepared, for example, by mixing an electrode mixture solvent, powdered electrode material, and a binder. The powdered electrode material may be further dispersed or mixed into the obtained electrode mixture. The obtained electrode mixture is then uniformly applied to a current collector such as a metal foil or metal mesh, dried, and pressed as necessary to form a thin electrode mixture layer on the current collector, thus creating a thin-film electrode. Alternatively, the powdered electrode material and binder may be mixed first, and then the electrode mixture solvent may be added to prepare the electrode mixture.
[0158] (Electrode mixture layer) An electrode mixture layer can be fabricated using the electrode mixture of this disclosure. Since the electrode mixture layer of this disclosure is formed from the above-mentioned electrode mixture, it is possible to obtain a battery in which metal components are less likely to leach out, gas generation is less likely, and excellent cycle characteristics can be obtained.
[0159] Furthermore, according to this disclosure, An electrode mixture layer containing an amide compound (A), a powder electrode material, and a binder, If the amide compound (A) is a compound other than N-methyl-2-pyrrolidone, The content of the amide compound (A) is 0.0001 to 100 ppb by mass relative to the mass of the electrode mixture layer. An electrode mixture layer is provided.
[0160] Since the electrode mixture layer of this disclosure contains a very small amount of an amide compound (A) other than N-methyl-2-pyrrolidone, metal components are less likely to leach out, and furthermore, gas generation is less likely, and a battery with excellent cycle characteristics can be obtained.
[0161] The amide compound (A), powder electrode material, and binder contained in the electrode mixture layer of this disclosure are all similarly preferred to be those described above as the amide compound (A), powder electrode material, and binder contained in the electrode mixture of this disclosure.
[0162] The content of the amide compound (A), powder electrode material, and binder in the electrode mixture layer is preferably 99.0 to 100% by mass, more preferably 99.5% by mass or more, even more preferably 99.9% by mass or more, and still more preferably 99.99% by mass or more, relative to the mass of the electrode mixture layer.
[0163] The ratio of electrode active material to conductive additive in the electrode mixture layer is preferably 80:20 to 99.5:0.5 by mass ratio, and more preferably 90:10 to 99.5:0.5.
[0164] The ratio of powder electrode material to binder in the electrode mixture layer is preferably 80:20 to 99.5:0.5 by mass ratio, more preferably 90:10 to 99.5:0.5, and even more preferably 95:5 to 99.5:0.5, and is determined considering the retention of powder components, adhesion to the current collector, and conductivity of the electrode.
[0165] The content of amide compound (A) in the electrode mixture layer is preferably 0.0001 to 100 ppb by mass, more preferably 0.0005 ppb by mass or more, even more preferably 0.0010 ppb by mass or more, more preferably 50 ppb by mass or less, even more preferably 10 ppb by mass or less, still more preferably 5.0 ppb by mass or less, and particularly preferably 2.0 ppb by mass or less, relative to the mass of the electrode mixture layer.
[0166] The electrode mixture layer can be manufactured, for example, by uniformly applying an electrode mixture containing an electrode mixture solvent, powdered electrode material, and binder to a current collector such as a metal foil or metal mesh, drying it, and pressing it as necessary.
[0167] The density of the electrode mixture layer is preferably 2.0 to 5.0 g / cm³. 3 More preferably 2.5 to 4.5 g / cm³ 3 That is the case.
[0168] The density of the electrode mixture layer can be calculated from the mass and volume of the electrode mixture layer.
[0169] The thickness of the electrode mixture layer is preferably 20 μm or more, more preferably 30 μm or more, even more preferably 40 μm or more, particularly preferably 45 μm or more, preferably 170 μm or less, and more preferably 150 μm or less, in order to obtain even higher battery characteristics.
[0170] The thickness of the electrode mixture layer can be measured using a micrometer. In this disclosure, the thickness of the electrode mixture layer is the thickness per side when the electrode mixture layer is provided on both sides of the current collector.
[0171] Examples of current collectors include metal foils or metal meshes made of iron, stainless steel, copper, aluminum, nickel, titanium, etc., with aluminum foil being particularly preferred.
[0172] (Electrodes and batteries) The electrode mixtures and electrode mixture layers of this disclosure can be suitably used to form electrodes for electrochemical devices. The electrode of this disclosure comprises a current collector and the electrode mixture layer described above. The electrode mixture layer may be provided on one side of the current collector or on both sides. The electrode of this disclosure may be a positive electrode comprising a positive electrode mixture layer or a negative electrode comprising a negative electrode mixture layer, but it is preferably a positive electrode.
[0173] The electrode mixture and electrode mixture layer of this disclosure can be suitably used as materials for forming electrodes in batteries such as secondary batteries and capacitors. The battery may be a primary battery, a rechargeable battery (secondary battery), or an energy storage element. The battery may also be a non-aqueous electrolyte battery. Non-aqueous electrolyte batteries include all batteries that have an electrolyte and a power generation element. Examples of non-aqueous electrolyte batteries include lithium-ion primary batteries, lithium-ion secondary batteries, nickel-metal hydride batteries, lithium-ion capacitors, electric double-layer capacitors, and sodium-ion secondary batteries.
[0174] Furthermore, the present disclosure provides a secondary battery comprising the above-described electrode. In one embodiment, the battery of the present disclosure comprises an electrode having the above-described electrode mixture layer as the positive electrode.
[0175] Because the secondary battery of this disclosure is equipped with the above-mentioned electrodes, the leaching of metal components from the electrodes is suppressed, gas generation is less likely, and the battery exhibits excellent cycle characteristics.
[0176] The secondary battery of this disclosure comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, and it is preferable that one or both of the positive and negative electrodes are the electrodes described above. Furthermore, the secondary battery of this disclosure comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, and it is preferable that the positive electrode is the electrode described above. A separator may also be interposed between the positive and negative electrodes.
[0177] The non-aqueous electrolyte is not particularly limited, but one or more known solvents such as propylene carbonate, ethylene carbonate, monofluoroethylene carbonate, butylene carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propionate, and propyl propionate can be used. Any conventionally known electrolyte can also be used, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, LiN(CF3SO2)2, LiN(FSO2)2, NaClO4, NaAsF6, NaPF6, NaBF4, NaCl, NaBr, CH3SO3Na, CF3SO3Na, NaN(CF3SO2)2, NaN(FSO2)2, cesium carbonate, etc.
[0178] The electrodes of this disclosure are useful not only for lithium-ion and sodium-ion secondary batteries using liquid electrolytes as described above, but also for polymer electrolyte lithium secondary batteries, as well as for non-aqueous electrolyte secondary batteries. They are also useful for electric double-layer capacitors.
[0179] Although embodiments have been described above, it should be understood that various modifications to the form and details are possible without departing from the spirit and scope of the claims.
[0180] <1> According to the first aspect of this disclosure, A solvent for electrode mixtures containing an amide compound (A), If the amide compound (A) is a compound other than N-methyl-2-pyrrolidone, The content of amide compound (A) is 0.01 ppm by mass or more and less than 100 ppm by mass, relative to the mass of the solvent. A solvent for electrode mixtures is provided. <2> According to the second aspect of this disclosure, Furthermore, it contains N-methyl-2-pyrrolidone, The N-methyl-2-pyrrolidone content is 90.0% by mass or more relative to the mass of the solvent. A solvent for electrode mixtures from a first perspective is provided. <3> According to the third aspect of this disclosure, Amide compound (A) has general formula (1): [ka] (In the formula, R 1 , R 2 and R 3 R is independently an H or monovalent substituent, however R 1 , R 2 and R 3 The total number of carbon atoms is 4 or less, R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. 1 , R 2 and R 3 A solvent for an electrode mixture according to a first or second view is provided, which is a compound represented by (where any two of the compounds may be bonded together to form a ring). <4> According to the fourth aspect of this disclosure, A solvent for an electrode mixture is provided, according to any one of the first to third aspects, wherein the amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide. <5> According to the fifth aspect of this disclosure, An electrode mixture containing a solvent for electrode mixtures according to any of the first to fourth aspects is provided. <6> According to the sixth aspect of this disclosure, Furthermore, an electrode mixture according to a fifth aspect is provided, which contains a powder electrode material and a binder. <7> According to the seventh aspect of this disclosure, A sixth aspect of electrode mixtures is provided, wherein the powder electrode material is at least one selected from the group consisting of lithium composite oxide, sodium composite oxide, and conductive additive. <8> According to the eighth aspect of this disclosure, The aforementioned powder electrode material contains a lithium composite oxide, and the lithium composite oxide is General formula (7): Li yNi 1-x M x O2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) An electrode mixture according to a sixth or seventh aspect is provided, which is a lithium-nickel composite oxide represented by [formula]. <9> According to the ninth aspect of this disclosure, The powder electrode material contains a sodium composite oxide, and the sodium composite oxide is General formula (8):Na z M 0 O2 (In the formula, z is 0.01 <z≦1であり、M 0 (This represents a metal atom, excluding Na.) An electrode mixture according to any of the sixth to eighth aspects is provided, which is a sodium complex oxide represented by [the formula shown]. <10> According to the tenth aspect of this disclosure, An electrode mixture is provided according to any 6th to 9th aspect, wherein the powder electrode material contains a conductive additive, and the conductive additive is at least one selected from the group consisting of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphene. <11> According to the eleventh aspect of this disclosure, The electrode mixture is provided according to any of the 6th to 10th views, wherein the binder contains a fluorine-containing polymer containing vinylidene fluoride units. <12> According to the 12th aspect of this disclosure, The binder contains at least one selected from the group consisting of polyvinylidene fluoride, and fluorine-containing copolymers containing vinylidene fluoride units and other monomer units other than vinylidene fluoride, and the other monomers are at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, hexafluoropropylene, and fluoroalkyl vinyl ether. The electrode mixture according to any one of the 6th to 11th aspects is provided. <13> According to the thirteenth aspect of the present disclosure, Further, the present invention provides an electrode mixture containing a powdery electrode material and a binder, The amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide, The content of the amide compound (A) is 0.01 mass ppm or more and 60 mass ppm or less relative to the mass of the solvent, The binder is at least one selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride / tetrafluoroethylene copolymer, and vinylidene fluoride / (meth)acrylic acid copolymer, The powdery electrode material contains a positive electrode active material and a conductive auxiliary agent, The positive electrode active material General formula (7): Li y Ni 1-x M x O2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦1.2, and M represents a metal atom (excluding Li and Ni)). A lithium-nickel-based composite oxide represented by: or General formula (8): Na z M 0 O2 (wherein z is 0.01<z≦1, and M 0 represents a metal atom (excluding Na)). A sodium composite oxide represented by: The conductive auxiliary agent is carbon black An electrode mixture is provided according to any of the 5th to 12th aspects. <14> According to the fourteenth aspect of this disclosure, An electrode mixture layer is provided, formed from an electrode mixture according to any of the 5th to 13th aspects. <15> According to the 15th aspect of this disclosure, An electrode mixture layer containing an amide compound (A), a powder electrode material, and a binder, If the amide compound (A) is a compound other than N-methyl-2-pyrrolidone, The content of the amide compound (A) is 0.0001 to 100 ppb by mass relative to the mass of the electrode mixture layer. An electrode mixture layer is provided. <16> According to the sixteenth aspect of this disclosure, Amide compound (A) has general formula (1): [ka] (In the formula, R 1 , R 2 and R 3 R is independently an H or monovalent substituent, however R 1 , R 2 and R 3 The total number of carbon atoms is 4 or less, R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. 1 , R 2 and R 3 A fifteenth aspect of an electrode mixture layer is provided, which is a compound represented by (where any two of the compounds may be bonded together to form a ring). <17> According to the seventeenth aspect of this disclosure, An electrode mixture layer is provided in which the amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide. <18> According to the 18th aspect of this disclosure, An electrode mixture layer is provided according to any 15th to 17th aspect, wherein the powder electrode material is at least one selected from the group consisting of lithium composite oxide, sodium composite oxide, and conductive additive. <19> According to the 19th aspect of this disclosure, The aforementioned powder electrode material contains a lithium composite oxide, and the lithium composite oxide is General formula (7): Li y Ni 1-x M x O2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) An electrode mixture layer is provided, which is a lithium-nickel composite oxide represented by any of the 15th to 18th aspects. <20> According to the 20th aspect of this disclosure, The powder electrode material contains a sodium composite oxide, and the sodium composite oxide is General formula (8):Na z M 0 O2 (In the formula, z is 0.01 <z≦1であり、M 0 (This represents a metal atom, excluding Na.) An electrode mixture layer is provided, which is a sodium composite oxide represented by any of the 15th to 19th aspects. <21> According to the 21st aspect of this disclosure, An electrode mixture layer is provided, according to any 15th to 20th viewpoint, wherein the powder electrode material contains a conductive additive, and the conductive additive is at least one selected from the group consisting of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphene. <22> According to the 22nd aspect of this disclosure, An electrode mixture layer is provided, according to any 15th to 21st viewpoint, wherein the binder is a fluorine-containing polymer containing vinylidene fluoride units. <23> According to the 23rd aspect of this disclosure, An electrode mixture layer is provided according to any 15th to 22nd viewpoint, wherein the binder is at least one selected from the group consisting of polyvinylidene fluoride and fluorine-containing copolymers containing vinylidene fluoride units and other monomer units other than vinylidene fluoride, and the other monomer is at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, hexafluoropropylene, and fluoroalkyl vinyl ether. <24> According to the 24th aspect of this disclosure, The amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide. The content of amide compound (A) is 0.0001 to 50 ppb by mass relative to the mass of the electrode mixture layer. The binder is at least one selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride / tetrafluoroethylene copolymer, and vinylidene fluoride / (meth)acrylic acid copolymer. The aforementioned powder electrode material contains a positive electrode active material and a conductive additive, The positive electrode active material is General formula (7): Li y Ni 1-x M x O2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) Lithium-nickel composite oxides represented by, General formula (8):Na z M 0 O2 (In the formula, z is 0.01 <z≦1であり、M 0 (This represents a metal atom, excluding Na.) This is a sodium complex oxide represented by the following: The conductive additive is carbon black. An electrode mixture layer is provided according to any of the 15th to 23rd aspects. <25> According to the 25th aspect of the present disclosure, There is provided an electrode comprising the electrode mixture layer according to any one of the 14th to 24th aspects. <26> According to the 26th aspect of the present disclosure, There is provided a battery comprising the electrode according to the 25th aspect. [Examples]
[0181] Next, the embodiments of the present disclosure will be described with reference to Examples, but the present disclosure is not limited to only such Examples.
[0182] Each numerical value in the Examples was measured by the following methods.
[0183] (Polymer Composition) The compositions of the fluorine-containing copolymer and PVdF were measured by a solution NMR method. Measurement apparatus: VNMRS400 manufactured by Varian, Inc. Resonance frequency: 376.04 (Sfrq) Pulse width: 30° (pw=6.8)
[0184] (Content of polar group-containing monomer unit in PVdF) The content of the polar group-containing monomer unit (acrylic acid unit) in PVdF was measured by acid-base titration of carboxyl groups. Specifically, approximately 0.5 g of PVdF was dissolved in acetone at a temperature of 70 to 80°C. 5 mL of water was added dropwise under vigorous stirring so as to avoid coagulation of PVdF. At the neutralization transition at approximately -270 mV, titration was performed with an aqueous NaOH solution having a concentration of 0.1 N until complete neutralization of acidity. From the measurement results, the amount of substance of the polar group-containing monomer unit contained in 1 g of PVdF was determined, and the content of the polar group-containing monomer unit was calculated.
[0185] (Weight average molecular weight) The molecular weight was measured by gel permeation chromatography (GPC). Using a Tosoh HLC-8320GPC and a column (three SuperAWM-H columns connected in series), dimethylformamide (DMF) was flowed at a flow rate of 0.3 ml / min. The weight-average molecular weight was calculated from the data obtained (reference: polystyrene).
[0186] (Melting point) Using a differential scanning calorimetry (DSC) system, the temperature corresponding to the maximum value in the heat of fusion curve was determined when the temperature was increased from 30°C to 220°C at a rate of 10°C / min, then decreased to 30°C at 10°C / min, and then increased again to 220°C at a rate of 10°C / min.
[0187] (Binding agent) In the examples and comparative examples, polymers having the following properties were used as binders. In Tables 1 and 2, the polymer content indicates the percentage (mass%) of each polymer when the total mass of the binder is set to 100% by mass.
[0188] Polymer A: VdF homopolymer Weight average molecular weight 800,000 Melting point 170℃
[0189] Polymer B: PVdF containing acrylic acid units Acrylic acid content: 1.5 mol% Weight average molecular weight 1.4 million Melting point 170℃
[0190] Polymer C: PVdF containing acrylic acid units Acrylic acid content: 0.5 mol% Weight average molecular weight 1.2 million Melting point 170℃
[0191] Polymer D: Fluorine-containing copolymer containing VdF units and TFE units VdF / TFE = 88 / 12 (mol%) Weight average molecular weight 1.2 million Melting point 130℃
[0192] (Cathode active material) The following positive electrode active materials were used in the examples and comparative examples. NMC811: LiNi 0.8 Mn 0.1 Co 0.1 O2 NCA:LiNi 0.82 Co 0.15 Al 0.03 O2 Na(Ni 0.33 Fe 0.33 Mn 0.33 )O2
[0193] (Conductive additive) The following conductive additives were used in the examples and comparative examples. Ketjenblack, SuperP Li, manufactured by Timcal.
[0194] (Negative electrode active material) The following negative electrode active materials were used in the examples and comparative examples. Graphite powder Mixed powder of graphite powder / SiO powder (85 / 15 (mass ratio)) Hard carbon
[0195] (solvent) In the examples and comparative examples, solvents were used in which amide compound (A) was added to N-methyl-2-pyrrolidone in the amounts listed in Tables 1 to 3. Furthermore, 2-pyrrolidone, N-methylpropionamide (MPA), and N-ethylpyrrolidone (NEP) were used as compound (A). The amounts of compound (A) listed in Tables 1-3 are the total amounts when two or more types of compound (A) are used. In Examples 16 and 21, MPA and 2-pyrrolidone were added at a solvent ratio of 5 ppm each.
[0196] Examples 1-21, Comparative Examples 1-4 A pouch-type lithium-ion secondary battery was fabricated using the method described below, and its battery characteristics were evaluated.
[0197] [Fabrication of the positive electrode] In Examples 1-16 and Comparative Examples 1-2, NMC811 was used as the positive electrode active material. In Examples 17-21 and Comparative Examples 3-4, NCA was used as the positive electrode active material.
[0198] A positive electrode mixture was prepared by mixing a binder, a positive electrode active material, a conductive additive, and a solvent containing the amide compound (A) listed in Tables 1 and 2. The mass ratio of the positive electrode active material, conductive additive, and binder was 97 / 1.5 / 1.5. The solid content concentration in the positive electrode mixture was 75% by mass. The obtained positive electrode mixture was uniformly applied to one side of a positive electrode current collector (aluminum foil with a thickness of 20 μm), and after drying at 120°C for 60 minutes to volatilize N-methyl-2-pyrrolidone, a positive electrode comprising a positive electrode mixture layer and a positive electrode current collector was fabricated by pressing with a pressure of 10 tons using a roll press machine.
[0199] Tables 1 and 2 show the content of amide compound (A) relative to the mass of the solvent (ppm) and the content of amide compound (A) relative to the mass of the positive electrode mixture layer (ppb). The content of amide compound (A) relative to the mass of the positive electrode mixture layer (ppb) was determined by extraction with hexane, concentration, and measurement by gas chromatography-mass spectrometry.
[0200] [Fabrication of the negative electrode] In Examples 1-16 and Comparative Examples 1-2, artificial graphite was used as the negative electrode active material. In Examples 17-21 and Comparative Examples 3-4, a mixed powder of graphite powder and silica powder was used as the negative electrode active material.
[0201] A negative electrode mixture slurry was prepared by mixing an aqueous dispersion of sodium carboxymethylcellulose (1% by mass) as the negative electrode active material and thickener, and an aqueous dispersion of styrene-butadiene rubber (50% by mass) as the binder, in an aqueous solvent with a solid content ratio of 0.97 / 1.5 / 1.5 (by mass). This slurry was then applied uniformly to one side of a 10 μm thick copper foil, dried, and then compressed and formed using a press to create the negative electrode.
[0202] [Cell creation] As described above, the positive electrode, negative electrode, and polypropylene separator were stacked in the order of negative electrode, separator, and positive electrode to create a battery element. This battery element was then inserted into a bag made of laminate film, which consisted of an aluminum sheet (40 μm thick) coated on both sides with a resin layer, with the terminals of the positive and negative electrodes protruding. The electrolyte (a solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3 / 7, in which LiPF6 was dissolved at a concentration of 1 mol / liter, and vinylene carbonate was further added at a concentration of 2 mass%) was injected into each bag, and the bags were vacuum-sealed to create a pouch-type lithium-ion secondary battery.
[0203] [Cycle Test] In Examples 1-16 and Comparative Examples 1-2, the pouch-type lithium-ion secondary batteries manufactured as described above were CC / CV charged to 4.25V with a current equivalent to 0.1C at 25°C (0.05C cut-off), then discharged to 3.0V with a constant current of 0.1C. This constituted one cycle, and five formation cycles were performed. Subsequently, 300 cycles of constant current-constant voltage charging at 0.5C and constant current discharge (between 4.25V and 3.0V) were performed in a constant temperature bath at 60°C. The ratio of the discharge capacity at 300 cycles to the discharge capacity at 60°C was calculated and defined as the cycle capacity retention rate (%). (Discharge capacity after 300 cycles) / (Discharge capacity in the first cycle) × 100 = Cycle capacity retention rate (%)
[0204] In Examples 17-21 and Comparative Examples 3-4, the pouch-type lithium-ion secondary batteries manufactured as described above were CC / CV charged to 4.35V with a current equivalent to 0.1C at 25°C (0.05C cut-off), then discharged to 2.5V with a constant current of 0.1C. This constituted one cycle, and five formation cycles were performed. Subsequently, constant current-constant voltage charging at 0.5C and constant current discharge (between 4.35V and 2.5V) were performed 500 times in a constant temperature bath at 60°C. The ratio of the discharge capacity at 500 cycles to the discharge capacity at 60°C was calculated and defined as the cycle capacity retention rate (%). (Discharge capacity after 500 cycles) / (Discharge capacity in the first cycle) × 100 = Cycle capacity retention rate (%)
[0205] [Evaluation of gas generation amount] The volume of the battery before and after the cycle test was measured using the Archimedes method, and the amount of gas generated was determined from the volume change before and after the cycle test. Examples 1-16 and Comparative Examples 1-2 (Battery volume after 300 cycles) - (Battery volume after 1 cycle) = Gas generation amount (ml) Examples 17-21 and Comparative Examples 3-4 (Battery volume after 500 cycles) - (Battery volume after 1 cycle) = Gas generation amount (ml)
[0206] [Evaluation of metal leaching] After measuring the discharge capacity, the cell was disassembled, the negative electrode was washed with dimethyl carbonate (DMC), and then the negative electrode was immersed in dilute nitric acid to dissolve the transition metal. The amount of metal was quantified by ICP emission spectrometry of the filtrate of this dilute nitric acid. The quantified value (amount of metal deposited on the negative electrode) was assumed to be the amount of metal leached from the positive electrode.
[0207] In Examples 1-16 and Comparative Examples 1-2, the amount of Mn eluted was quantified. In Examples 17-21 and Comparative Examples 3-4, the amount of Ni eluted was quantified.
[0208] The results are shown in Tables 1 and 2.
[0209] [Table 1]
[0210] [Table 2]
[0211] Example 22, Comparative Example 5 A pouch-type sodium-ion secondary battery was fabricated using the method described below, and its battery characteristics were evaluated.
[0212] [Fabrication of the positive electrode] In Example 22 and Comparative Example 5, Na(Ni) was used as the positive electrode active material. 0.33 Fe 0.33 Mn 0.33 O2 was used.
[0213] A positive electrode mixture was prepared by mixing a binder, a positive electrode active material, a conductive additive, and a solvent containing the amide compound (A) listed in Table 3. The mass ratio of the positive electrode active material, conductive additive, and binder was 96 / 2 / 2. The solid content concentration in the positive electrode mixture was 70% by mass. The obtained positive electrode mixture was uniformly applied to one side of a positive electrode current collector (aluminum foil with a thickness of 20 μm), and after drying at 120°C for 60 minutes to volatilize N-methyl-2-pyrrolidone, a positive electrode comprising a positive electrode mixture layer and a positive electrode current collector was fabricated by pressing with a pressure of 10 tons using a roll press machine.
[0214] Table 3 shows the content of amide compound (A) relative to the mass of the solvent (ppm) and the content of amide compound (A) relative to the mass of the positive electrode mixture layer (ppb). The content of amide compound (A) relative to the mass of the positive electrode mixture layer (ppb) was determined by extraction with hexane, concentration, and measurement by gas chromatography-mass spectrometry.
[0215] [Fabrication of the negative electrode] In Example 22 and Comparative Example 5, hard carbon was used as the negative electrode active material.
[0216] A negative electrode mixture slurry was prepared by mixing an aqueous dispersion of sodium carboxymethylcellulose (1% by mass) as the negative electrode active material and thickener, and an aqueous dispersion of styrene-butadiene rubber (50% by mass) as the binder, in an aqueous solvent with a solid content ratio of 0.97 / 1.5 / 1.5 (by mass). This slurry was then applied uniformly to one side of a 10 μm thick copper foil, dried, and then compressed and formed using a press to create the negative electrode.
[0217] [Cell creation] As described above, the positive electrode, negative electrode, and polypropylene separator were stacked in the order of negative electrode, separator, and positive electrode to create a battery element. This battery element was inserted into a bag made of laminate film, which consists of an aluminum sheet (40 μm thick) coated on both sides with a resin layer, with the terminals of the positive and negative electrodes protruding. Then, electrolyte (a solvent in which propylene carbonate, ethylene carbonate, and ethyl methyl carbonate are mixed in a volume ratio of 1 / 2 / 5, with NaPF6 dissolved at a concentration of 1 mole / liter) was injected into each bag, and the bags were vacuum sealed to create a pouch-type sodium-ion secondary battery.
[0218] [Cycle Test] In Example 22 and Comparative Example 5, the pouch-type sodium-ion secondary batteries manufactured above were CC / CV charged to 3.8V with a current equivalent to 0.1C at 25°C (0.05C cut-off), and then discharged to 2.6V with a constant current of 0.1C. This constituted one cycle, and five formation cycles were performed. Subsequently, constant current-constant voltage charging at 0.5C and constant current discharge (between 3.8V and 2.6V) were performed 200 times in a constant temperature bath at 60°C. The ratio of the discharge capacity at 200 cycles to the discharge capacity at 60°C was calculated and defined as the cycle capacity retention rate (%). (Discharge capacity after 200 cycles) / (Discharge capacity in the first cycle) × 100 = Cycle capacity retention rate (%)
[0219] [Evaluation of gas generation amount] The volume of the battery before and after the cycle test was measured using the Archimedes method, and the amount of gas generated was determined from the volume change before and after the cycle test. Example 22 and Comparative Example 5 (Battery volume after 200 cycles) - (Battery volume after 1 cycle) = Gas generation amount (ml)
[0220] [Evaluation of metal leaching] After measuring the discharge capacity, the cell was disassembled, the negative electrode was cleaned with DMC, and then the negative electrode was immersed in dilute nitric acid to dissolve the transition metal. The amount of metal was quantified by ICP emission spectrometry of the filtrate of this dilute nitric acid. The quantified value (amount of metal deposited on the negative electrode) was assumed to be the amount of metal leached from the positive electrode.
[0221] In Example 22 and Comparative Example 5, the amount of Mn eluted was quantified.
[0222] The results are shown in Table 3.
[0223] [Table 3]
Claims
1. A solvent for electrode mixtures containing an amide compound (A), The amide compound (A) is a compound other than N-methyl-2-pyrrolidone. The content of amide compound (A) is 0.01 ppm by mass or more and less than 100 ppm by mass, relative to the mass of the solvent. Solvent for electrode mixtures.
2. Furthermore, it contains N-methyl-2-pyrrolidone, The N-methyl-2-pyrrolidone content is 90.0% by mass or more relative to the mass of the solvent. The solvent for electrode mixture according to claim 1.
3. Amide compound (A) has general formula (1): 【Transformation 5】 (wherein, R 1 , R 2 and R 3 are each independently H or a monovalent substituent, provided that the total number of carbon atoms of R 1 , R 2 and R 3 is 4 or less, and at least one of R 1 , R 2 and R 3 is an organic group having a carbonyl group. Any two of R 1 , R 2 and R 3 may be bonded to each other to form a ring.) The solvent for an electrode mixture according to claim 1, which is a compound represented by the formula.
4. The solvent for electrode mixture according to claim 1, wherein the amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide.
5. An electrode mixture containing the solvent for electrode mixtures described in claim 1.
6. Furthermore, the electrode mixture according to claim 5 further contains a powder electrode material and a binder.
7. The electrode mixture according to claim 6, wherein the powder electrode material is at least one selected from the group consisting of lithium composite oxide, sodium composite oxide, and conductive additive.
8. The aforementioned powder electrode material contains a lithium composite oxide, and the lithium composite oxide is General form (7): Li y Ni 1-x M x O 2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) The electrode mixture according to claim 6, which is a lithium-nickel composite oxide represented by [the specified term].
9. The powder electrode material contains a sodium composite oxide, and the sodium composite oxide is General form (8): Na z M 0 O 2 (In the formula, z is 0.01 < z ≤ 1, M 0 (This represents a metal atom, excluding Na.) The electrode mixture according to claim 6, which is a sodium complex oxide represented by the following:
10. The electrode mixture according to claim 6, wherein the powder electrode material contains a conductive additive, and the conductive additive is at least one selected from the group consisting of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphene.
11. The electrode mixture according to claim 6, wherein the binder contains a fluorine-containing polymer containing vinylidene fluoride units.
12. The electrode mixture according to claim 6, wherein the binder contains at least one selected from the group consisting of polyvinylidene fluoride and fluorine-containing copolymers containing vinylidene fluoride units and other monomer units other than vinylidene fluoride, and the other monomer is at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, hexafluoropropylene, and fluoroalkyl vinyl ether.
13. Furthermore, an electrode mixture containing powder electrode material and a binder, The amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide. The content of amide compound (A) is 0.01 ppm by mass or more and 60 ppm by mass or less, relative to the mass of the solvent. The binder is at least one selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride / tetrafluoroethylene copolymer, and vinylidene fluoride / (meth)acrylic acid copolymer. The aforementioned powder electrode material contains a positive electrode active material and a conductive additive, The positive electrode active material is General form (7): Li y Ni 1-x M x O 2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) Lithium-nickel composite oxides represented by, General form (8): Na z M 0 O 2 (In the formula, z is 0.01 < z ≤ 1, M 0 (This represents a metal atom, excluding Na.) This is a sodium complex oxide represented by the following: The conductive additive is carbon black. The electrode mixture according to claim 5.
14. An electrode mixture layer formed from the electrode mixture according to claim 5.
15. An electrode mixture layer containing an amide compound (A), a powder electrode material, and a binder, The amide compound (A) is a compound other than N-methyl-2-pyrrolidone. The content of the amide compound (A) is 0.0001 to 100 ppb by mass relative to the mass of the electrode mixture layer. Electrode mixture layer.
16. Amide compound (A) has general formula (1): 【Transformation 6】 (In the formula, R 1 , R 2 and R 3 R is independently an H or a monovalent substituent, where R 1 , R 2 and R 3 The total number of carbon atoms is 4 or less, R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. 1 , R 2 and R 3 The electrode mixture layer according to claim 15, wherein any two of the compounds may be bonded together to form a ring.
17. The electrode mixture layer according to claim 15, wherein the amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide.
18. The electrode mixture layer according to claim 15, wherein the powder electrode material is at least one selected from the group consisting of lithium composite oxide, sodium composite oxide, and conductive additive.
19. The aforementioned powder electrode material contains a lithium composite oxide, and the lithium composite oxide is General form (7): Li y Ni 1-x M x O 2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) The electrode mixture layer according to claim 15, which is a lithium-nickel composite oxide represented by [the specified].
20. The powder electrode material contains a sodium composite oxide, and the sodium composite oxide is General form (8): Na z M 0 O 2 (In the formula, z is 0.01 < z ≤ 1, M 0 (This represents a metal atom, excluding Na.) The electrode mixture layer according to claim 15, which is a sodium composite oxide represented by the formula.
21. The electrode mixture layer according to claim 15, wherein the powder electrode material contains a conductive additive, and the conductive additive is at least one selected from the group consisting of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphene.
22. The electrode mixture layer according to claim 15, wherein the binder is a fluorine-containing polymer containing vinylidene fluoride units.
23. The electrode mixture layer according to claim 15, wherein the binder is at least one selected from the group consisting of polyvinylidene fluoride and fluorine-containing copolymers containing vinylidene fluoride units and other monomer units other than vinylidene fluoride, and the other monomer is at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, hexafluoropropylene, and fluoroalkyl vinyl ether.
24. The amide compound (A) is at least one selected from the group consisting of 2-pyrrolidone and N-methylpropionamide. The content of the amide compound (A) is 0.0001 to 50 ppb by mass relative to the mass of the electrode mixture layer. The binder is at least one selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride / tetrafluoroethylene copolymer, and vinylidene fluoride / (meth)acrylic acid copolymer. The aforementioned powder electrode material contains a positive electrode active material and a conductive additive, The positive electrode active material is General form (7): Li y Ni 1-x M x O 2 (In the formula, x is 0.01 ≤ x ≤ 0.7, y is 0.9 ≤ y ≤ 1.2, and M represents a metal atom (excluding Li and Ni).) Lithium-nickel composite oxides represented by, General form (8): Na z M 0 O 2 (In the formula, z is 0.01 < z ≤ 1, M 0 (This represents a metal atom, excluding Na.) This is a sodium complex oxide represented by the following: The conductive additive is carbon black. The electrode mixture layer according to claim 15.
25. An electrode comprising an electrode mixture layer according to any one of claims 14 to 24.
26. A battery comprising the electrode described in claim 25.
Citation Information
Patent Citations
Battery electrode components
JP2023505931A